Effect of Outpatient Education on Blood Glucose Profile of Type 2 Diabetes Mellitus Patients Based on the Results of Continuous Glucose Monitoring - ZHOU Xiao, ZHOU Yunting, KONG Xiaocen, LIU Xiaomei, YUAN Lu, JING Ting, WANG Weiping, LI Huiqin (Zhongguo quanke yixue, 2024)
Background Continuous glucose monitoring (CGM) is rarely applied to outpatient treatments. The impact of CGM-based diabetes education to change unhealthy living and eating habits on the blood glucose profile is still unclear. Objective Based on the retrospective results of CGM, outpatient education such as diet and exercise was applied to outpatients with type 2 diabetes mellitus (T2DM) who were managed by oral hypoglycemic drugs. This study aims to evaluate the effects on blood glucose profiles. Methods A total of 88 outpatient T2DM patients medicated with oral hypoglycemic drugs in the Department of Endocrinology, Nanjing First Hospital in 2021 were included and managed by CGM, involving 60 male and 28 female patients. The enrolled patients maintained the original hypoglycemic treatment regimen and lifestyle habits on the 1st to 3rd day. On the 4th day, we downloaded and analyzed CGM data and provided outpatient education based on individualized eating habit and exercise. On the 6th day, the CGM sensor and recorder were removed. CGM data on the 2nd day versus 5th day were compared for dynamic blood glucose profiles, including the 24 h mean blood glucose (MBG), mean amplitude of glycemic excursion (MAGE) and time in target glucose range (TIR) . Results Based on the CGM results, MBG in outpatients with T2DM on the 5th day after outpatient education was significantly reduced from (8.34±1.97) mmol/L to (7.85±1.65) mmol/L (P<0.05). TIR was significantly elevated from (78.21±24.64) % to (84.28±21.87) % (P<0.05). Moreover, MAGE was significantly reduced from (4.53±2.25) mmol/L to (3.80±1.80) mmol/L (P<0.05). Stratified by the course of T2DM, MBG after outpatient education significantly decreased in both patients with T2DM course <10 years (n=62) and those with T2DM course ≥10 years (n=26) than the baseline before education (P<0.05). After outpatient education, the standard deviation (SD), MAGE and target glucose range (TAR) were significantly reduced, while TIR was significantly elevated in patients with T2DM course <10 years (P<0.05). Stratified by age, MBG and TAR after outpatient education were significantly reduced in both patients aged <65 years old (n=55) and those aged ≥65 years old (n=33) than the baseline before education, while TIR was significantly elevated (P<0.05). SD and MAGE were significantly reduced after outpatient education in patients aged <65 years old (P<0.05) . Conclusion Based on CGM results, outpatient education such as diet and exercise could effectively improve MBG, TIR levels, and blood glucose variability in outpatient T2DM patients using oral hypoglycemic drugs. Patients with less than 10 years of T2DM course and younger than 65 years of age gain more clinical benefits.